Scaling up AIDS treatment in developing countries : a review of current and future arguments - Kovsted, Jens (2005)
Presents six key arguments made against scaling up Highly Active Antiretrovial Treatment (HAART) in developing countries. Focuses on two potentially very importment future issues related to the scaling up of HAART, both of which could become a source of dispute and conflict in the near future.